1977
DOI: 10.1029/gl004i005p00189
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observation of internal wave refraction in the South China Sea

Abstract: A visible image for 21 May 1973 obtained from the DMSP satellite suggests the occurrence of internal waves refracting around the Pratas Islands in the South China Sea. Arguments are presented suggesting that the waves are tidally forced along the density interface prevalent for that area during the spring season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…The waves increase the surface roughness in areas where the horizontal flow converges, allowing for their view in the glint zone. Solitons have been observed via satellite imagery in the sun glint zone [34,35]-the DNB can now provide similar high spatial resolution views of solitons during the nighttime hours via moon glint in a way entirely analogous to daytime sun glint. Figure 6 compares thermal infrared VIIRS imagery (M15) to DNB imagery for a southern portion of the Celebes Sea, located in the Indonesian archipelago.…”
Section: Sea Surface Roughness Properties Via Moon Glintmentioning
confidence: 99%
“…The waves increase the surface roughness in areas where the horizontal flow converges, allowing for their view in the glint zone. Solitons have been observed via satellite imagery in the sun glint zone [34,35]-the DNB can now provide similar high spatial resolution views of solitons during the nighttime hours via moon glint in a way entirely analogous to daytime sun glint. Figure 6 compares thermal infrared VIIRS imagery (M15) to DNB imagery for a southern portion of the Celebes Sea, located in the Indonesian archipelago.…”
Section: Sea Surface Roughness Properties Via Moon Glintmentioning
confidence: 99%
“…Since Fett and Rabe (1977) showed that there existed internal waves in the vicinity of Dongsha Islands in the SCS by a satellite photograph in May 1973, some progress has been made on the studies of the internal solitons here. The wave-induced current reported here may exceed 200 cm s -1 (Cai et al, 2002).…”
Section: Summary Of the Recent Observations Of Internal Solitons Nearmentioning
confidence: 99%
“…In the last two decades, it is reported that the internal solitons near Dongsha Islands in the northern South China Sea (SCS) were very active (Fett and Rabe, 1977;Fang et al, 2000) . It is pointed out that the solitons north of Dongsha Islands were generated in a strait between Batan and Sabtang islands in the Luzon Strait (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately these satellites view the same areas only once every 18 days. Some work has been done by Fett and Rabe (1977) and Fett etal. (1978) using visible data from satellites of the Defense Meteorological Satellite Program (DMSP).…”
Section: Introductionmentioning
confidence: 99%